13 - Ecrire l’histoire du mouvement de résistance à la colonisation : un enjeu historiographique à Madagascar - Denis Alexandre Lahiniriko, (Afrika Zamani, 2022)
Since the commemoration of the fiftieth anniversary of 1947 uprising in Madagascar, history, as a scientific discipline, has reached the public stage. There is an emergence of a history need, leading research to step outside the framework of University’s amphitheatre. Now, the malagasy historian will play an increasingly important role in public debate. Various «interpretations» of the nationalist movement that fought against colonial domination since its beginning in the 1910s have lead to this «public enthusiasm». Indeed, for a long time, Malagasy historians and historians of Madagascar studied and presented Malagasy nationalism as a monolithic ideological tendency. In a rather simplistic and Manichean view, they believe the struggle for independence is of «all», without exception, colonized. But in recent years, a new generation of historians emerged in Madagascar. A generation that has neither seen nor experienced the colonialism or the French neocolonialism. They are rather sensitive to the political anomie that Madagascar has experienced since its independence, as the difficulty of the country to establish a true democracy. Thus, in their thinking about colonization and its various oppressive aspects, as on the Malagasy liberation movement, they tend to qualify particular «acquired» historian knowledge on Malagasy nationalism. This article focuses on the evolution of not only historian knowledge on Malagasy nationalism in general and 1947 uprising in particular but also of Malagasy historiography related to these two themes. Finally, we would also like to bring up the current debate generated by these two evolutions. In this case, to assess the importance of the interference that collective memory has on the writing of history is one of key goal.